Population genetic analysis of autophagy and phagocytosis genes in Drosophila melanogaster and D. simulans. - Im, J.H.; Lazzaro, B.P. (PLoS ONE, 2018)
Autophagy and phagocytosis are cellular immune mechanisms for internalization and elimination of intracellular and extracellular pathogens. Some pathogens have evolved the ability to inhibit or manipulate these processes, raising the prospect of adaptive reciprocal co-evolution by the host. We performed population genetic analyses on phagocytosis and autophagy genes in Drosophila melanogaster and D. simulans to test for molecular evolutionary signatures of immune adaptation. We found that phagocytosis and autophagy genes as a whole exhibited an elevated level of haplotype homozygosity in both species. In addition, we detected signatures of recent selection, notably in the Atg14 and Ykt6 genes in D. melanogaster and a pattern of elevated sequence divergence in the genderblind (gb) gene on the D. simulans lineage. These results suggest that the evolution of the host cellular immune system as a whole may be shaped by a dynamic conflict between Drosophila and its pathogens even without pervasive evidence of strong adaptive evolution at the individual gene level.